How does teacher training research contribute to the construction of pedagogical knowledge? (Educational Perspectives Magazine (REPED), 2023)
This paper refers to some of the characteristics of research in the area of teacher training in Chile and its problematic elements. It locates the explanations in this respect in an extemal perspective that addresses the necessary conditions to investígate. Notwithstanding, it looks towards the interior of the investigative processes, their meaning, orientation and focus. The paper intends to establish a link between these conditions of investigation and the configuration of the pedagogical knowledge as the centralizing axis of the processes of teacher training.
Keywords: Teacher Training, Educational Research, Pedagogical Knowledge.